Application of the Simple, Fast and Light Cost Principles in the Determination of Time for Case Settlement in the Religious Court / Syar’iyah Court in Perspective of Maqashid Syari’ah - Siregar, Dangas; Pagar, Pagar; Harahap, Arifuddin Muda (JURNAL AKTA, 2023)
Courts under the Supreme Court of the Republic of Indonesia are always in the spotlight of the public and the media both about their performance and about the weaknesses and shortcomings in these institutions as judicial institutions that carry out the mandate of the provisions of the law. the determination of the time period for case settlement in various courts including the Religious Courts and the Syar’iyah Court quickly as mandated by the provisions of the Law which regulates that judicial procedures must be based on the principles of simple, fast and light costs. In reality, in judicial proceedings that take place in the Religious Courts and in the Syar’iyah Court, not always the principles of simplicity, speed and low cost can be applied. Often there are cases whose resolution takes a protracted time so that the litigants themselves certainly feel tired of undergoing all the existing judicial processes. When viewed from the point of view of Islamic law, a decision / law that is born by humans must actually be in line with the intent and purpose of the Islamic law itself or known as Maqashid al-Syari’ah. In this study using the type of library research (library research), the object of this research is a court decision, the nature of this research is Descriptive-analytic and Qualitative Data Analysis. The results of the study concluded that from the point of view of Maqashid al-Syari’ah, the application of the principles of simple, fast and light costs in case settlement in the Religious Courts and the Syar’iyah Court is classified as the application of Maqashid at the hajiyyah level, namely to provide convenience for justice seekers in obtaining access to justice as fair as possible.